CER16 Inhibits Post-Transcriptional Gene Silencing of CER3 to Regulate Alkane Biosynthesis. Issue 3 (15th January 2020) - Yang, Xianpeng; Feng, Tao; Li, Shipeng; Zhao, Huayan; Zhao, Shuangshuang; Ma, Changle; Jenks, Matthew A.; Lü, Shiyou
Abstract : Alkane biosynthesis in cuticular wax of Arabidopsis associated with stress responses is regulated through an RNA quality control mechanism. Abstract: The aerial surfaces of land plants have a protective layer of cuticular wax. Alkanes are common components of these waxes, and their abundance is affected by a range of stresses. The CER16 protein has been implicated in alkane biosynthesis in the cuticular wax of Arabidopsis ( Arabidopsis thaliana ). Here, we identified two new mutant alleles of CER16 in Arabidopsis resulting in production of less wax with dramatically fewer alkanes than the wild type. Map-based cloning with genetic analysis revealed that the cer16 phenotype was caused by complete loss of AT5G44150, encoding a protein with no known domains or motifs. Comparative transcriptomic analysis revealed that transcripts of CER3, previously shown to play a principal role in alkane production, were markedly reduced in the cer16 mutants. To define the relationship between CER3 and CER16, we transformed the full CER3 gene into a cer16 mutant. Transgenic CER3 expression was silenced, and levels of small interfering RNAs targeting CER3 were significantly increased. Mutating two major components of the RNA-silencing machinery in a cer16 genetic background restored CER3 transcript levels to wild-type levels, with the stems restored to wild-type glaucousness. We suggest that CER16 deficiency induces post-transcriptional gene silencing of both endogenous and exogenous expression of CER3 .